1988
DOI: 10.1111/j.1365-2923.1988.tb00796.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a teaching skills improvement programme for residents

Abstract: This study addressed three evaluation questions about the effectiveness of a workshop to teach residents how to teach: (1) How do residents evaluate their own teaching skills? (2) How do students evaluate residents' teaching skills? (3) Do residents of various specialties differ in their teaching skills? One hundred and five residents rated their skills on the Inventory of Teaching Behavior significantly higher after attending the workshop than before it. Third-year students evaluated the teaching skills of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 8 publications
0
19
1
Order By: Relevance
“…[6][7][8] The OSTE scores for residents involved in the reinforcement intervention, taken 8 months after their RATs workshop, were as high or higher than those of control group residents examined 3 weeks after the workshops. A number of factors may have contributed to the finding that students generally rated the residents higher than the residents themselves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] The OSTE scores for residents involved in the reinforcement intervention, taken 8 months after their RATs workshop, were as high or higher than those of control group residents examined 3 weeks after the workshops. A number of factors may have contributed to the finding that students generally rated the residents higher than the residents themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated studies have shown that teaching skills degrade over time without reinforcement (eg, .6 months [6][7][8] ), and we hypothesized that if the reinforcement system was effective, degradation would be prevented and there would be no significant difference in the performance of both groups. A two-tailed Student t-test was performed of the overall mean across stations, followed by tests of differences of the 6 stations.…”
Section: Assessment Of Skill Deteriorationmentioning
confidence: 99%
“…Most of these recommendations have been based on the assumption that better teaching skills do not only improve medical residents' professional competence (Kates and Lesser, 1985;Apter et al, 1988;Busari et al, 2002Busari et al, , 2003 but probably also enhance the effectiveness of undergraduate clinical training. There are reports in the literature that in institutions where such programmes have been implemented, improvements in the didactic skills and perceived teaching qualities of medical residents have been achieved (Lawson and Harvill, 1980;Jewett et al, 1982;Camp and Hoban, 1988;Edwards et al, 1988;Meleca and Pearsol, 1988; Busari (submitted for publication); Bing You and Greenberg, 1990;Sheets et al, 1991). However, many of these studies did not use standardized methods in developing and evaluating the training programmes.…”
Section: Introductionmentioning
confidence: 91%
“…Resident evaluations demonstrated that objectives were met and that residents were confident in their ability to apply new skills, mirroring other studies' results of resident as teacher programs. [16][17][18] Finally, evaluation of our 3-phase model allowed identification of lessons learned for implementation and delivery of a resident educator curriculum program (B O X 2).…”
Section: Discussionmentioning
confidence: 99%